Readiness to work after six months post-stroke in Subang Jaya / Aida Yasmin Sameri and Padma A. Rahman - Sameri, Aida Yasmin; A. Rahman, Padma (Faculty of Health Sciences, Universiti Teknologi MARA, 2024)
The low rate of return to work (RTW) among stroke survivors despite receiving rehabilitation treatment has been documented in few previous studies. This study aims to identify the relationship between demographic profiles and readiness to return to work and also to determine stages of employment readiness to return to work of post-stroke patients after 6 months of intervention. A total of 61 participants of post-stroke patients recruited from five private centers in Subang Jaya participated in the survey with a mean age of 47.57 (SD=5.74), ranging from 36 years old to 55 years old. The LAM Assessment of Stages of Employment Readiness (LASER) is chosen as the main instrument in this study. Chi-square was used to analyze the relationship between demographic data and stages of readiness. Meanwhile, descriptive statistics was used to determine the stages of readiness after 6 months post-stroke. The result showed that the demographic characteristics of gender, marital status, being the sole income of the family, type of stroke, stage of stroke, changes in salary after stroke, age, duration of stroke and duration of therapy received had no significant difference with stages of employment readiness. This study also found that most of the participants are in the pre-contemplation stage (37.7%, n=23) where they might not be ready to return to work yet, followed by the contemplation stage (34.4%, n=21) and lastly, the action stage (27.9%, n=17). In conclusion, health care professions such as occupational therapy should emphasize personalized strategies to address psychosocial barriers, as most stroke survivors remain in early stages of readiness to return to work post-rehabilitation.